Synthesis and evaluation of the HIF-1α inhibitory activities of novel ursolic acid tetrazole derivatives. Issue 12 (15th June 2019) - Zhang, Lin-Hao; Zhang, Zhi-Hong; Li, Ming-Yue; Wei, Zhi-Yu; Jin, Xue-Jun; Piao, Hu-Ri
Graphical abstract: Highlights: Eight series of ursolic acid-tetrazole derivatives were designed and synthesized. The inhibitory activity on HIF-1α pathway and cytotoxicity of these compounds were evaluated. Compound 14a is a promising lead for searching effective HIF-1α inhibitors. The investigation of dose-dependently inhibiting the luciferase activity in Hep3B cells of compound 14a was performed. Abstract: The hypoxia-inducible factor-1α (HIF-1α) pathway has been implicated in tumor angiogenesis, growth, and metastasis. Therefore, the inhibition of this pathway is an important therapeutic target for the treatment of various types of cancers. Here, we designed and synthesized 31 ursolic acid (UA) derivatives containing a tetrazole moiety and evaluated them for their potential anti-tumor activities as HIF-1α transcriptional inhibitors. Of these, compound 14d (IC50 0.8 ± 0.2 µM) displayed the most potent activity and compounds 14a (IC50 4.7 ± 0.2 µM) exhibited the most promising biological profile. Analysis of the structure–activity relationships of these compounds with HIF-1α suggested that the presence of a tetrazole group located at C-28 of the UA derivatives was critical for their inhibitory activities.